Nitric Oxide Alleviated Arsenic Toxicity by Modulation of Antioxidants and Thiol Metabolism in Rice (Oryza sativa L.) - Singh, Amit P.; Dixit, Garima; Kumar, Amit; Mishra, Seema; Singh, Pradyumna K.; Dwivedi, Sanjay; Trivedi, Prabodh K.; Chakrabarty, Debasis; Mallick, Shekhar; Pandey, Vivek; Dhankher, Om P.; Tripathi, Rudra D. (Frontiers in Plant Science, 2016)
Nitric oxide is a gaseous signalling molecule and has a profound impact on plant growth and development. It is reported to serve as pro oxidant as well as antioxidant in plant system. In present study, we evaluated the protective role of nitric oxide against AsV toxicity in rice plants. Arsenate exposure has hampered the plant growth, reduced the chlorophyll content and enhanced the oxidative stress while the exogenous NO supplementation has reverted these symptoms. Nitric oxide supplementation has reduced the As accumulation in root as well as shoot. Nitric oxide supplementation to AsV exposed plants has reduced the gene expression level of OsLsi1 and OsLsi2. Arsenate stress significantly impacted thiol metabolism, it reduced GSH content and GSH/GSSG ratio and enhanced the level of PCs. Nitric oxide supplementation maintained the GSH/GSSG ratio and reduced the level of PCs. Nitric oxide supplementation reverted AsV induced iron deficiency in shoot and had significant impact of gene expression level of various iron transporters (OsYSL2, OsFRDL1, OsIRT1 and OsIRO2). Conclusively, exogenous application of nitric oxide could be advantageous against AsV toxicity and could confer the tolerance to AsV stress in rice.